Consensus Statement by the American Association of Clinical Endocrinologists and American College of Endocrinology on the Comprehensive Type 2 Diabetes Management Algorithm – 2019 Executive Summary - Garber, Alan J.; Abrahamson, Martin J.; Barzilay, Joshua I.; Blonde, Lawrence; Bloomgarden, Zachary T.; Bush, Michael A.; Dagogo-Jack, Samuel; DeFronzo, Ralph A.; Einhorn, Daniel; Fonseca, Vivian A.; Garber, Jeffrey R.; Garvey, W. Timothy; et al. (Endocrine practice, 2019)
This algorithm for the comprehensive management of persons with type 2 diabetes (T2D) was developed to provide clinicians with a practical guide that considers the whole patient, his or her spectrum of risks and complications, and evidence-based approaches to treatment. It is now clear that the progressive pancreatic beta-cell defect that drives the deterioration of metabolic control over time begins early and may be present before the diagnosis of T2D (1-3). In addition to advocating glycemic control to reduce microvascular complications, this document highlights obesity and prediabetes as underlying risk factors for the development of T2D and associated macrovascular complications. In addition, the algorithm provides recommendations for blood pressure (BP) and lipid control, the two most important risk factors for atherosclerotic cardiovascular disease (ASCVD). Since originally drafted in 2013, the algorithm has been updated as new therapies, management approaches, and important clinical data have emerged. The current algorithm includes up-to-date sections on lifestyle therapy and all classes of obesity, antihyperglycemic, lipidlowering, and antihypertensive medications approved by the U.S. Food and Drug Administration (FDA) through December 2018. This algorithm supplements the American Association of Clinical Endocrinologists (AACE) and American College of Endocrinology (ACE) 2015 Clinical Practice Guidelines for Developing a Diabetes Mellitus Comprehensive Care Plan (4) and is organized into discrete sections that address the following topics: the founding principles of the algorithm, lifestyle therapy, obesity, prediabetes, management of hypertension and dyslipidemia, and glucose control with noninsulin antihyperglycemic agents and insulin. In the accompanying algorithm, a chart summarizing the attributes of each antihyperglycemic class appears at the end.